2005
DOI: 10.2486/indhealth.43.241
|View full text |Cite
|
Sign up to set email alerts
|

Biodynamic Response at the Palm of the Human Hand Subjected to a Random Vibration

Abstract: This study investigated the biodynamic response (BR) distributed at the palm of the hand subjected to a random vibration. Twelve male subjects were used in the experiment. Each subject applied three coupling actions (grip-only, push-only, and combined grip and push) on a simulated tool handle at three different levels (50, 75, and 100 N) of palm force. This study found that the hand-arm system resonated mostly in the frequency range of 20 to 50 Hz, depending on the specific test treatment and individual charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Both the driving-point response data 13,47,67,70) and the vibration transmissibility data 53,54,71) indicate that the resonance of the system in the z h -direction 7) (along the forearm direction) is usually in the range of 16 to 63 Hz, depending the applied force and hand and arm postures. This resonant feature supports the proposed palm theoretical model 49) . It, however, contradicts the flat response phenomenon shown in some previously reported data 63) .…”
Section: Major Problems and Improvements Of Measurement Methodssupporting
confidence: 75%
See 3 more Smart Citations
“…Both the driving-point response data 13,47,67,70) and the vibration transmissibility data 53,54,71) indicate that the resonance of the system in the z h -direction 7) (along the forearm direction) is usually in the range of 16 to 63 Hz, depending the applied force and hand and arm postures. This resonant feature supports the proposed palm theoretical model 49) . It, however, contradicts the flat response phenomenon shown in some previously reported data 63) .…”
Section: Major Problems and Improvements Of Measurement Methodssupporting
confidence: 75%
“…The results also show that the eigen-frequency corresponding to a specific mode increased almost linearly with the magnitude of the static deformation, irrespective of the mode of vibration. The simulations are consistent in their trends with the experimental observations by many investigators 13,[46][47][48][49] , who reported that the resonant frequencies of the fingers and hand increased with increases in the applied forces.…”
Section: ) Finite Element Modelingsupporting
confidence: 80%
See 2 more Smart Citations
“…These differences could have affected in a different way the biodynamic response of the finger-hand-arm system during vibration exposure and the vibration transmissibility to the target muscles (Aldien et al 2006;Dong et al 2004Dong et al , 2005. This leads us to conjecture that the higher effective palm force while pushing the vibratory bar might have favored a larger vibration power transmission to the upper extremity (Dong et al 2005) compared with pulling, which in turn resulted in greater agonist activation of the TB. However, the observed vibration-induced increase in TB agonist activation was only significant at the higher f out of 42 Hz.…”
Section: Discussionmentioning
confidence: 94%